Perancangan User Experience Aplikasi Mobile Penunjang Budidaya Lele Menggunakan Metode Human Centered Design Pada PT. MaksiPlus Utama Indonesia - Burhanuddin Ali Ahmadi; Herman Tolle; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
MaksiPlus Utama Indonesia (MUI) is a company in Indonesia that is engaged in distribution of fisheries, agriculture, animal husbandry. In the fisheries, PT. MUI collaborate with catfish aquaculture entrepreneurs in conducting catfish aquaculture. In the management of catfish aquaculture there are various problems that can effected in the development of catfish aquaculture including, catfish condition data are not recorded regularly and neatly because conventional recording tools has many deficiency, feeding catfish that sometimes is late, and the amount of food provided does not match the daily catfish requirements. One of solution to overcome these problems is to use technology in the form of a mobile application which is expected to support the management of catfish aquaculture. Therefore, the goal of this study is to design a user experience for mobile applications that support catfish aquaculture, so that the application has a good, comfortable and easy to use user experience before being developed into a ready-to-use product. By implementing the Human Centered Design method until the solution design evaluation stage, designing the user experience is done. Usability Testing method is used to evaluate the results of the design in the form of a prototype to assess aspects of learnability, efficiency, and satisfaction. Obtained a value of 99% which means that it is above the average standard in the learnability aspect, efficiency aspect is 0.12 (task/second), and the satisfaction aspect obtained a score of 80 which means a high level of satisfaction with a grade B and good adjective ratings